Deep brain stimulation of the anterior nucleus of the thalamus for seizures after new-onset refractory status epilepticus: a case report - Sasaki, Ryota; Ohara, Hiroya; Kinoshita, Masako; Iizuka, Takahiro; Tamura, Kentaro; Nagata, Kiyoshi; Nakagawa, Ichiro (Frontiers in Human Neuroscience, 2025)
ObjectivesMost patients with new-onset refractory status epilepticus (NORSE) subsequently develop drug-resistant epilepsy (DRE) with multiple seizure foci and are not the typical candidates for resective surgery. We report the first case of DRE developing after cryptogenic-NORSE (C-NORSE) that was successfully treated using deep brain stimulation targeting the anterior nucleus of the thalamus (ANT-DBS).MethodsA 52-year-old man developed C-NORSE at the age of 45 years and presented with sequelae of DRE and cognitive dysfunction despite anti-seizure medications and immunotherapy administration. Seizure semiology comprised palpitations, chills, and nausea, followed by impairment of awareness with oral automatism multiple times a day. Video-electroencephalogram monitoring (vEEG) showed bilateral independent electrographic seizures (ESz) in the fronto-temporal areas. He underwent ANT-DBS. Preoperative and postoperative vEEG recordings for 3 days were compared.ResultsPreoperative vEEG showed 11 clinical seizures correlated with ESz. The duration of ESz ranged from 55 to 213 s (median, 81 s). Three months after ANT-DBS stimulation, vEEG showed four subclinical ESz episodes lasting from 22 to 31 s (median, 25.5 s) (Mann–Whitney U test, p = 0.001). The patient had not developed an overt clinical seizure until the last follow-up at 9 months. No adverse events were observed during treatment.ConclusionANT-DBS is an effective treatment option for DRE after NORSE, particularly when the epileptogenic network is located in the temporal lobe. A detailed evaluation using vEEG is useful for identifying the epileptogenic foci and assessing therapeutic outcome. Immunomodulatory mechanisms via cytokines could play roles in the pathogenesis of development of DRE after NORSE and seizure suppression effect of ANT-DBS.